The deubiquitinase OTUD1 regulates immunoglobulin production and proteasome inhibitor sensitivity in multiple myeloma - Vdovin, Alexander; Jelinek, Tomas; Zihala, David; Sevcikova, Tereza; Durech, Michal; Sahinbegovic, Hana; Snaurova, Renata; Radhakrishnan, Dhwani; Turi, Marcello; Chyra, Zuzana; Popkova, Tereza; Venglar, Ondrej; et al. (Nature communications, 2022)
Serum monoclonal immunoglobulin (Ig) is the main diagnostic factor for patients with multiple myeloma (MM), however its prognostic potential remains unclear. On a large MM patient cohort (n = 4146), we observe no correlation between serum Ig levels and patient survival, while amount of intracellular Ig has a strong predictive effect. Focused CRISPR screen, transcriptional and proteomic analysis identify deubiquitinase OTUD1 as a critical mediator of Ig synthesis, proteasome inhibitor sensitivity and tumor burden in MM. Mechanistically, OTUD1 deubiquitinates peroxiredoxin 4 (PRDX4), protecting it from endoplasmic reticulum (ER)-associated degradation. In turn, PRDX4 facilitates Ig production which coincides with the accumulation of unfolded proteins and higher ER stress. The elevated load on proteasome ultimately potentiates myeloma response to proteasome inhibitors providing a window for a rational therapy. Collectively, our findings support the significance of the Ig production machinery as a biomarker and target in the combinatory treatment of MM patients.
Keywords: Deubiquitinating Enzymes; Proteasome Inhibitors; Proteasome Endopeptidase Complex; specifické proteázy ubikvitinu; bortezomib; inhibitory proteasomu; proteasomový endopeptidasový komplex; Multiple Myeloma; imunoglobuliny; deubikvitinasy; proteomika; Bortezomib; lidé; Humans; apoptóza; Ubiquitin-Specific Proteases; Proteomics; mnohočetný myelom; Immunoglobulins; Apoptosis